Opa-interacting protein 5 modulates docetaxel-induced cell death via regulation of mitophagy in gastric cancer - Tae Woo Kim; Seon-Jin Lee; Young-Jun Park; Sang Yoon Park; Byung Moo Oh; Yun Sun Park; Bo-Yeon Kim; Young-Ha Lee; Hee Jun Cho; Suk Ran Yoon; Yong-Kyung Choe; Hee Gu Lee (Tumor Biology)
Damage to mitochondria induces mitophagy, a cellular process that is gaining interest for its therapeutic relevance to a variety of human diseases. However, the mechanism underlying mitochondrial depolarization and clearance in mitophagy remains poorly understood. We previously reported that mitochondria-induced cell death was caused by knockdown of Neisseria gonorrhoeae opacity-associated-interacting protein 5 in gastric cancer. In this study, we show that Neisseria gonorrhoeae opacity-associated-interacting protein 5 loss and gain of function modulates mitophagy induced by treatment with docetaxel, a chemotherapy drug for gastric cancer. The activation of mitophagy by Neisseria gonorrhoeae opacity-associated-interacting protein 5 overexpression promoted cell survival, preventing docetaxel-induced mitochondrial clearance. Conversely, short interfering RNA–mediated knockdown of Neisseria gonorrhoeae opacity-associated-interacting protein 5 accelerated docetaxel-induced apoptosis while increasing mitochondrial depolarization, reactive oxygen species, and endoplasmic reticulum stress and decreasing adenosine triphosphate production. We also found that the mitochondrial outer membrane proteins mitofusin 2 and phosphatase and tensin homolog–induced putative kinase 1 colocalized with Neisseria gonorrhoeae opacity-associated-interacting protein 5 in mitochondria and that mitofusin 2 knockdown altered Neisseria gonorrhoeae opacity-associated-interacting protein 5 expression. These findings indicate that Neisseria gonorrhoeae opacity-associated-interacting protein 5 modulates docetaxel-induced mitophagic cell death and therefore suggest that this protein comprises a potential therapeutic target for gastric cancer treatment.